Introducing more transparent and efficient land management in post‐socialist cities: Lessons from Kyrgyzstan - Kaganova, Olga; Akmatov, Abdirasul; Undeland, Charles (International Journal of Strategic Property Management, 2010)
The Urban Institute (UI) worked with five cities in post‐Soviet Kyrgyzstan to apply better management practices through the development of Strategic Land Management Plans. Kyrgyzstan transferred property to local governments, but municipal land management had remained poor owing to a proliferation of responsible agencies, lack of rule of law, corruption, and passiveness on the part of local governments. UI worked with local governments to make an inventory of municipal land, publicize the results, and develop a strategy that articulated principles for land management and an implementation plan. This led to several improvements including proper registration of parcels and proactive policies to lease and sell land through open competition. It also established a model for determining public policy that countered corruption and public deliberation of costs and benefits in the use of local assets. Donor involvement to promote good land legislation, the property registration system, and decentralization was also critical to success.First published online: 18 Oct 2010